2003
DOI: 10.1046/j.1365-2443.2003.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐induced hexameric ring structure of the cyanobacterial circadian clock protein KaiC

Abstract: ATP-induced KaiC hexamerization is necessary for the clock function of KaiC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
151
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 30 publications
8
151
0
Order By: Relevance
“…In the presence of ATP, KaiC forms a hexamer (Hayashi et al 2003). We examined the potential for KaiC monomer exchange between two KaiC hexamers using FLAGtagged KaiC.…”
Section: A Sequential Program Of Kaic Phosphorylationmentioning
confidence: 99%
“…In the presence of ATP, KaiC forms a hexamer (Hayashi et al 2003). We examined the potential for KaiC monomer exchange between two KaiC hexamers using FLAGtagged KaiC.…”
Section: A Sequential Program Of Kaic Phosphorylationmentioning
confidence: 99%
“…We determined the three-dimensional structure of KaiC by single particle analysis of cryoelectron microscopic images and demonstrated that the hexamer has a hexagonal, pot-shaped structure composed of six identical dumbbell-shaped subunits (6). The two spherical regions of the dumbbell-shaped structure probably correspond to the two domains of KaiC (6).…”
mentioning
confidence: 99%
“…To elucidate the mechanism of Kai protein-based generation of circadian oscillations in cyanobacteria, we analyzed the proteins derived from the thermophilic cyanobacterium Thermosynechococcus elongatus BP-1 by biochemical (5-7), structural (6,7), and biophysical techniques (7). T. elongatus cells grow at over 50°C, and their stable heat-tolerant proteins are suitable for analyses.…”
mentioning
confidence: 99%
See 2 more Smart Citations